PRESCRIPTION’S COMPLIANCE OVERVIEW IN ADMINISTRATIVE, PHARMACEUTICAL, AND CLINICAL ASPECTS AT PHARMACY DEPOT IN CLINIC X IN DEPOK CITY - Wibowo, Putri Larasati; Ilmi, Primayanti Nurul; Harfiani, Erna; Pradana, Dhigna Luthfiyani Citra (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2024)
Medication error is any incident that occurs during the treatment process that can jeopardize a patient's life, result in inappropriate healthcare services, and fundamentally can be prevented at various stages of treatment The National Patient Safety Map report states that medication administration errors rank first (24.8%) among the top 10 reported incidents of medication errors.Bottom of Form Top of FormBottom of Form The main duty of a pharmacist is to prevent errors in the use of medication or medication errors. Prevention includes steps such as reviewing prescriptions. The standards used are regulated by Minister of Health Regulation Number 73 of 2016, where prescription review activities include administrative review, pharmaceutical suitability, and clinical considerations. The purpose of this study is to determine the completeness of prescriptions in terms of administrative, pharmaceutical, and clinical aspects at Pharmacy X. The method used in this research is descriptive with a retrospective approach. There were 255 patient prescription data that met the study criteria. The compliance of prescriptions at Pharmacy X is still not fulfilled in terms of patient weight (0%), doctor's telephone number (0%), dosage form (16.1%), and drug strength (40%). However, the potential for drug interactions in prescriptions at Pharmacy X is quite good, with 23 out of 255 prescriptions (9%) indicating potential interactions.